دراسة تأثير إضافة هباب الفحم وكربونات الكالسيوم وبعض أنواع الأكاسيد على الخواص الترايبولوجية لمركبات البولي استر غير المشبع - أحمد سلامة; رامي منصور; هبة غدير (Tishreen University, 2019)
This research aims to study the effect of addition of some types of inorganic  fillers (aluminum oxide, magnesium oxide, titanium oxide, carbon black and calcium carbonate) on the friction and wear properties of unsaturated polyester composites and on the surface hardness. To achieve this goal, the samples of polyester matrix composites reinforced with different weight fractions and various percentages of the filler used were prepared. The results showed that there were different effects of the  additives used, especially on the volume loss (∆V). The results showed that the best  results were obtained in the composites containing CaCO3. The effect of these additive materials was also studied on surface hardness. There was a clear improvement in the surface hardness values and the results were best obtained when using the TiO2. يهدف هذا البحث إلى دراسة تأثير إضافة بعض أنواع المالئات اللا عضوية (أوكسيد الألمنيوم، أوكسيد المغنزيوم، أوكسيد التيتانيوم، هباب الفحم وكربونات الكالسيوم) على خواص الاحتكاك والاهتراء لمركبات البولي استر غير المشبع، وعلى القساوة السطحية. لتحقيق هذا الهدف تم تحضير عينات من مادة الأساس البوليميرية الحاوية على نسب مختلفة من المالئات المستخدمة. أظهرت نتائج الاختبارات وجود تأثيرات متباينة لمواد الإضافة ولاسيما على مقدار الفقد الحجمي (ΔV) حيث تم الحصول على أفضل النتائج في المركبات الحاوية على كربونات الكالسيوم. تم دراسة تأثير مواد الإضافة هذه أيضاً على القساوة السطحية فتبين حدوث تحسن واضح بقيم القساوة السطحية وأن أفضل النتائج تم الحصول عليها عند استخدام أوكسيد التيتانيوم.